To solve the system of linear equations:
- \(4h + 4s = 10\)
- \(7h + 5s = 15\)
Let's first simplify the first equation.
Divide the entire first equation by 4:
\[ h + s = \frac{10}{4} \] \[ h + s = 2.5 \quad \text{(Equation 1)} \]
Now we can express \(s\) in terms of \(h\):
\[ s = 2.5 - h \quad \text{(Equation 2)} \]
Next, substitute Equation 2 into the second equation:
\[ 7h + 5(2.5 - h) = 15 \]
Distributing the 5:
\[ 7h + 12.5 - 5h = 15 \]
Combine like terms:
\[ 2h + 12.5 = 15 \]
Now, subtract 12.5 from both sides:
\[ 2h = 15 - 12.5 \] \[ 2h = 2.5 \]
Divide both sides by 2:
\[ h = 1.25 \]
Now, substitute \(h\) back into Equation 2 to find \(s\):
\[ s = 2.5 - 1.25 \] \[ s = 1.25 \]
Thus, the solution is:
\[ h = 1.25 \] \[ s = 1.25 \]
Final answers:
\(h = $1.25\)
\(s = $1.25\)